THE CEO OVERCONFIDENCE, INDUSTRY CHARACTERISTICS, AND FOREIGN OWNERSHIP: THEIR EFFECTS ON ESG DISCLOSURE - Shendy Gavriel Alexander; Tigor Tambunan (Bina Nusantara University, 2025)
Increasingly, business people believe that the CEO’s attitudes and behavior directly or indirectly impact the company’s sustainability. This phenomenon aligns with the increasing awareness of ESG management practices among stakeholders, particularly in large industries. Furthermore, the importance of sustainability in global conditions appears to underscore the role of foreign ownership in assessing company performance within the ESG framework. This quantitative study examines the influence of CEO overconfidence, industry characteristics, and foreign ownership on ESG disclosure using secondary data, consisting of 68 non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022. The sample was determined using purposive sampling and analyzed using multiple linear regression tests in EViews software. The listed company’s ESG score was obtained from Bloomberg. The results indicate that CEO overconfidence does not significantly affect ESG disclosure, suggesting that the complexity of these decisions is influenced by various internal and external factors beyond the CEO’s influence. Foreign ownership significantly influences ESG disclosure, with higher levels of foreign ownership correlating with broader disclosure, driven by the adoption of best practices and standards from international markets, alignment with foreign shareholder expectations, and fostering strong relationships. This study suggests that companies should focus on industry characteristics and foreign ownership and not overly worry about the impact of their CEO's overconfidence on ESG disclosure. Management should tailor their ESG disclosure strategies to align with unique industry characteristics to enhance the company's reputation and foster stronger stakeholder relationships.